2009
DOI: 10.1074/jbc.m109.012674
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Differentially Modulates the Activities of ERK, p38 MAPK, and JNK to Suppress Th17 and Th1 T Cell Differentiation in Type 1 Diabetic Mice

Abstract: Berberine, an alkaloid derivative from Berberis vulgaris L., has been used extensively in traditional Chinese medicine to treat diarrhea and diabetes, but the underlying mechanisms for treating diabetes are not fully understood. Recent studies suggested that berberine has many beneficial biological effects, including anti-inflammation. Because type 1 diabetes is caused by T cellmediated destruction of ␤ cells and severe islet inflammation, we hypothesized that berberine could ameliorate type 1 diabetes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
125
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 46 publications
11
125
1
Order By: Relevance
“…It also exhibits antitumor, antimicrobial, and even antidiabetic effects (31)(32)(33)(34)(35)(36). Moreover, a recent report suggested that BBR may be efficacious in experimental type I diabetes (37), raising the possibility of its use as a treatment for autoimmune diseases. This study was undertaken to investigate the novel regulatory properties and underlying mechanism of BBR in an autoimmune disease model.…”
mentioning
confidence: 99%
“…It also exhibits antitumor, antimicrobial, and even antidiabetic effects (31)(32)(33)(34)(35)(36). Moreover, a recent report suggested that BBR may be efficacious in experimental type I diabetes (37), raising the possibility of its use as a treatment for autoimmune diseases. This study was undertaken to investigate the novel regulatory properties and underlying mechanism of BBR in an autoimmune disease model.…”
mentioning
confidence: 99%
“…Although mice lacking T cells, B cells, and NK cells can still develop colitis in response to DSS (4,10), Th1/Th2 responses have been reported to modulate macrophage-induced inflammation in DSS-induced colitis model (9). Berberine has been reported to decrease Th17 and Th1 cytokine production and Th1 and Th17 cell differentiation in a Type 1 diabetic mouse model (8). Fig.…”
mentioning
confidence: 99%
“…Furthermore, berberine's immunoregulatory potentials have been demonstrated. Berberine has been shown to inhibit human immunodeficiency virus (HIV) protease inhibitor-induced TNF and IL-6 production in macrophages (45) and enhance progression of Type 1 diabetes in mice and decrease Th17 and Th1 cytokine production, and Th17 and Th1 cell differentiation by regulation of mitogen-activated protein kinase (MAPK) pathways in this mouse model (8).…”
mentioning
confidence: 99%
“…BBR was able to activate ERK1/2 signaling in mice as reported earlier [28]. We tested whether ERK1/2 pathway is involved in BBR-induced neuroprotective effects in PC12 cells.…”
Section: Bbr Stimulated the Erk1/2 Signaling Pathway In Pc12 Cellsmentioning
confidence: 94%